Menores retirados de sus hogares por la dinapen y su incidencia en el desarrollo integral del familiar - Zuque Méndez, Yara Cristina (2017)
For several years it has been seen that violence is part of the lives of children in their homes, today the behavior of children is silently carried in the home, on the streets, in schools and has become in a common practice and accepted socially, affecting mainly the development of the child, causing psychological problems that usually last throughout his life. The objective of this research is to prevent more abuse to minors occur in homes, and that the Dinapen, act immediately in cases of abuse in homes, to improve the quality of life of infants, and to develop a better communication between parents and children so that there are significant changes and achieve harmony between families, preventing more children being mistreated in their homes and thus be able to provide a better future for them, with a relationship and sustainable development between parents and children.